Chapter Magnetic Iron Oxide Colloids for Environmental Applications - Alvaro, Gallo-Cordova (InTechOpen, 2021)
This chapter deals with magnetic colloids with catalytic properties for the treatment of polluted waters and the efficient production of fuel alternatives. This kind of materials presents great advantages such as high surface/volume ratio, reproducibility, selectivity, ability to be magnetic harvested, functionalizable surfaces (e.g. with tunable pores and selective chelators deposited on them), high efficiencies and reusability. In particular, this chapter will consider the case of magnetic iron oxide colloids, which can be easily synthesized at low cost, are biocompatible and presents a well-developed surface chemistry. The most common techniques for the synthesis and functionalization of these magnetic nanoparticles will be reviewed and summarized. The iron oxide nanoparticles present outstanding properties that can be exploited in different aspect of the wastewater treatment such as heavy metals and organic pollutants removal by ionic exchange or adsorption, and degradation of the contaminants by advanced oxidation processes, among others. In the field of alternative energies, they have also been used as catalysts for biofuels production from oil crops, in Fischer-Tropsch reactions for liquid hydrocarbons and many other processes with potential environmental impact.